Analysis of Black Site and Black Spot at Jl. Daeng Manambon-Raden Kusno-Gusti Sulung Lelanang Section, Mempawah - Ratih, Ade; Kadarini, S. Nurlaily; Azwansyah, Heri (Fakultas Teknik Universitas Tanjungpura, 2024)
Transportation plays a vital role in society by facilitating the movement of people and goods. However, it also brings challenges like traffic congestion and accidents. With urbanization and increased vehicles, road safety has become crucial, as accidents have significant economic and social impacts. Analyzing accident-prone areas helps identify necessary preventive measures. This research was conducted on the 10.1 km Jl. Daeng Manambon-Raden Kusno-Gusti Sulung Lelanang section in Mempawah. Primary data from field surveys includes road conditions, fittings, geometry, and vehicle speeds. Secondary data is traffic accident data (2018-2023) from the Mempawah City Police, analyzed using numerical methods.The Jalan Daeng Manambon-Raden Kusno-Gusti Sulung Lelanang corridor analysis reveals several accident-prone areas (Black Spots) with damaged road features and poor safety facilities. Key findings include deteriorating zebra crossings, speed traps, and traffic signs. High-risk accident locations were identified using Z-Score and Cusum methods. Recommendations include repairing roads, repainting markings, installing better signage, and maintaining clear sightlines. Future studies should focus on more specific interventions and monitoring to improve road safety, following Department of Settlements and Regional Infrastructure guidelines for effective accident reduction